The Examination of Sports Injury and Career Anxiety Levels of Football Players - Hülya Cin; Onur Sarı; Cosmin Damian (Türk Spor ve Egzersiz Dergisi)
The aim of this study is to investigate the relationship between sport injury anxiety and career anxiety of amateur football players in Turkey. The study group of the research consists of 392 Amateur football players, 59 women and 333 men, who are actively participating in the competitions of the Turkish Football Federation in the 2021-2022 season. In this study, the “Sport Injury Anxiety Scale (SIAS)” and the “Career Anxiety Scale (CAS)” were used as data collection tools. In the study, descriptive statistical methods (percentage, frequency, mean, standard deviation), independent sample T-test, One-Way ANOVA analysis and Pearson Correlation were used to analyze the data. Depending on the findings there was a significant difference according to the being injured before and league variables in the SIAS mean scores of the participants, but there was no significant difference in the variable of family income in the SIAS mean scores of the participants. On the other hand, a statistically significant difference was found in the variables of family income and league in the CAS mean scores of the participants. And no statistically significant difference was found in the CAS mean scores of the participants according to the being injured before variable. The results of the correlation analysis showed that the mean scores of SIAS were in a significant, positive and moderate relationship with the mean scores of CAS. In conclusion, it has been revealed that as the sports injury anxiety level of amateur football players increase, their career anxiety levels also increase.